Employee fraud and misconduct: empirical evidence from a telecommunication company. (12th March 2018) - Nawawi, Anuar; Salin, Ahmad Saiful Azlin Puteh
Abstract : Purpose: The purpose of this study is to examine whether policies and procedures, one of the fundamental elements in the internal control environment, are adequate and effective in preventing fraud and unethical practices committed by employees of a company. In addition, this study attempts to assess the awareness and understanding of employees on the existence of relevant company policies and standard operating procedures for internal fraud and misconduct deterrence. Design/methodology/approach: Five cases from one Malaysian telecommunication company were randomly selected as a case study. Content analyses were conducted on actual cases of internal fraud and wrongdoings that were investigated and the enforcement that was discharged by the company. Findings: This study found that the company has sufficient policies and standard operating procedures to curb internal fraud and wrongdoing. However, they are ineffective and malfunction when responsible personnel violate or override the policies and procedures, irrespective of whether this is caused by carelessness, poor knowledge or clear intention to act dishonestly. Research limitations implications: This study was conducted on only one company with a limited number of investigated fraud cases. Access to higher number of fraud cases, particularly those that involved large amount of losses and considered as high-profile cases, were denied because of confidentiality. Practical implications: The study found that weak compliance to internal controls provides opportunities for fraud to occur, consistent with the fraud triangle theory. Fraud, committed both outside and inside an organization, can be considered as a worrying problem in the organization because of its severe impact on the reputation and bottom line figures of the company. The study provides important information to management to strengthen their compliance with the internal control system generally and policies and procedures particularly. Originality/value: This study is original, as it focuses on the actual fraud cases that occur in the telecommunication industry, which is under-researched in fraud literature, particularly in developing markets such as Malaysia. Prior empirical research on fraud and unethical practices has concentrated on factors that contribute to fraud and the financial and non-financial impacts of fraud in an organization.